Design of a Tandem Compressor for the Electrically-Driven Turbocharger of a Hybrid City Car - Nicolò Cuturi; Enrico Sciubba (Energies, 2021)
Within a broader national project aimed at the hybridization of a standard city car (the 998 cc Mitsubishi-derived gasoline engine of the Smart W451), our team tackled the problem of improving the supercharger performance and response. The originally conceived design innovation was that of eliminating the mechanical connection between the compressor and the turbine. In the course of the study, it turned out that it is also possible to modify both components to extract extra power from the engine and to use it to recharge the battery pack. This required a redesign of both compressor and turbine. First, the initial configuration was analyzed on the basis of the design data provided by the manufacturer. Then, a preliminary performance assessment of the turbocharged engine allowed us to identify three “typical” operating points that could be used to properly redesign the turbomachinery. It was decided to maintain the radial configuration for both turbine and compressor, but to redesign the latter by adding an inducer. For the turbine, only minor modifications to the nozzle guide vanes (NGV) and rotor blades shape were deemed necessary, while a more substantial modification was in order for the compressor. Fully 3-D computational fluid dynamics simulations of the rotating machines were performed to assess their performance at three operating points: the kick-in point of the original turbo (2000 rpm), the maximum power regime (5500 rpm), and an intermediate point (3500 rpm) close to the minimum specific fuel consumption for the original engine. The results presented in this paper demonstrate that the efficiency of the compressor is noticeably improved for steady operation at all three operating points, and that its choking characteristics have been improved, while its surge line has not been appreciably affected. The net energy recovery was also calculated and demonstrated interesting returns in terms of storable energy in the battery pack.